Analisa Pendapatan dan Gaya Hidup Terhadap Pola Konsumsi Masyarakat Singosaren Ponorogo - Rurin Dewi Anggraini (ISLAMIC BUSINESS and FINANCE (IBF), 2021)
This research was conducted because it saw the number of Islamic societies who behave consumptively and no longer pay attention to their Sharia as a Muslim. The number of factors that influence public consumption encourages researchers to know how the influence of income and lifestyle factors, Singosaren Ponorogo and to find out which factors have the most influence on the consumption of these people as a Muslim community. This research is a quantitative descriptive research. The population in this study is the Singosaren Ponorogo community who have fixed income and have worked for the past three years. By using interview techniques or interviews, the number of samples in this study amounted to 100 people. While the data analysis technique used is descriptive analysis with hypothesis testing carried out by multiple linear regression analysis with the SPSS 21 method. The results showed that income and lifestyle had a positive and significant effect on the consumption of Singosaren Ponorogo people. However, the income variable has the most dominant influence on the consumption of Singosaren Ponorogo people. From the regression results, the relation coefficient (R) shows that the independent variables (income and lifestyle) have a close relationship with the dependent variable (public consumption), a set of determination coefficients (R²) indicates a large influence between the independent variables and the dependent variable. Consumption made by the people of Singosaren is based on Islamic law, which is sourced from the Al-Quran and As-Sunnah according to the understanding of Salaf Ash-Salih (Manhaj Ahlusummah WalJamaah)